Author Correction: FAN1 interaction with ubiquitylated PCNA alleviates replication stress and preserves genomic integrity independently of BRCA2 - Antonio Porro (Nature Portfolio, 2017)
The financial support for this Article was not fully acknowledged. The Acknowledgements should have included the following: This study was in part supported by the Swiss National Foundation Grant No.: 31003A-156023 to Alessandro Sartori.